Implementing R-STEM and the ISLE Model to Enhance Students' Conceptual Understanding of Magnetic Induction at Unsyiah Laboratory School - Yulma Erma Yanti; Irwandi; Rini Safitri; Nizammuddin; Razief Perucha Fauzie Afidh; Muzakiah; Hasrati; Nurul Azmi; Ahmad Anwar Zainuddin; Amir ‘Aatieff Amir Hussain; Mohd Khairul Azmi Hassan (Jurnal Penelitian Pendidikan IPA, 2025)
Many schools face difficulties in implementing science education through a practicum due to insufficient laboratory facilities and bureaucratic constraints, which hinder students' hands-on learning. To address such constraints, a new web-based remote laboratory, Remote STEM (R-STEM) platform, was introduced by the STEM Research Center. This study explores using R-STEM in learning magnetic induction using the ISLE-based STEM approach with Student Activity Sheets (LKPD) to enhance engagement. A mixed-methods research design was utilized, and 72 high school students underwent a set of experiments according to the ISLE cycle, from observations to pattern detection, explanation, predictions, and experimentation verification. The results show a high rate of students’ understanding of magnetic induction, with a score in LKPD evaluation at 84%, a rate of implementation at 93%, and a score in learning activity alignment at 78.5%. In addition, pretest and posttest tests showed a learning outcome increase by 71%. This study contributes to the broader scientific educational community by demonstrating that remote laboratories can be effective in enhancing STEM learning, particularly in schools with fewer laboratory facilities.